Суб’єктність мобільних електронних пристроїв: природа, виробництво, практики - Дикань, Богдан Олександрович; Dykan, B.O. (Харьков, 2021)
Dykan B. O. Subjectivity of mobile electronic devices: nature, production, practices. – Qualifying scientific work on the rights of the manuscript. Dissertation for the degree of Doctor of Philosophy in specialty 054 – Sociology (Field of knowledge 05 – Social and behavioral sciences). – V. N. Karazin Kharkiv National University of the Ministry of Education and Science of Ukraine, Kharkiv, 2021. The urgency of the topic is due to the controversial and paradoxical situation in which, on the one hand, there is the mass distribution of mobile electronic devices for the vast majority of the population, and on the other hand – the decline of capabilities and ability of formal owners to control and understand. At the epistemological level, there is a contradiction in which at the level of human discourse and everyday practices, mobile electronic devices show new qualities, while sociology has not yet put forward an approach to defining, measuring, researching, quantifying, and qualifying these qualities.
Subjectivity of mobile electronic devices: nature, production, practices
Актуальність теми зумовлена контроверзійною та парадоксальною ситуацією, за якої, з одного боку, відбувається та відтворюється масове розповсюдження мобільних електронних пристроїв для переважної більшості населення, а з іншого боку – падіння можливостей та здатностей формальних власників контролювати та усвідомлювати вплив пристроїв на себе до кінця та повністю. На гносеологічному ж рівні виникає протиріччя, за якого на рівні дискурсу та повсякденних практик людей мобільні електронні пристрої проявляють нові якості, тоді як соціологія не висунула досі підходу до визначення, вимірювання, дослідження, квантифікації та кваліфікації цих якостей.
Keywords: суб’єктність; соціологія речей; фабрикація суб’єктності; фабрикована суб’єктність; випрацювана суб’єктність; екзогабітус; subjectivity; sociology of things; fabrication of subjectivity; fabricated subjectivity; elaborated subjectivity; exogabitus